The Effect Of Working Capital Management To Financial Performance Of The Company In Manufacturing Sector Listed In Indonesia Stock Exchange (Idx) Pe-riod 2013-2016 - Sarah Maysuri; Sholatia Dalimunthe (Fakultas Ekonomi, Universitas Negeri Jakarta, 2018)
This study aims to determine the effect of working capital management proxied by 5 independent variables, namely Working Capital Turnover (WCT), Cash Ratio (Csh R), Cash Conversion Cycle (CCC), Account Receivable Turnover (ARTO), and Inventory Turnover (ITO) on the company's financial performance in terms of profitability and market value which is equipped with Firm Size control variables in manufacturing companies listed on the IDX for the 2013-2016 period. The research method used is panel data regression using Random Effects Model and Fixed Effects Model. The results showed that only Csh R and CCC had a significant positive effect on Financial Performance with ROA proxy either with or without Firm Size control variables. Different results when compared to Financial Performance in terms of Tobin's market value using control variables, only (ITO) which proved to have a significant positive effect but without control variables found that (ARTO) and (ITO) also had a significant positive effect and the rest had no effect on Financial Performance manufacturing companies in the 2013-2016 period.